Multifunctional Supramolecular Hybrid Materials Constructed from Hierarchical Self‐Ordering of In Situ Generated Metal‐Organic Framework (MOF) Nanoparticles. (25th June 2015) - Chaudhari, Abhijeet K.; Han, Intaek; Tan, Jin‐Chong
<x xml:space="preserve">Abstract</x> A synergistic approach is described to engineer supramolecular hybrid materials based on metal‐organic frameworks, encompassing HKUST‐1 nanoparticles formed in situ, coexisting with an electrically conducting gel fiber network. The following findings are made: i) multistimuli‐responsive structural transformation via reversible sol–gel switching and ii) radical conversion of a soft hybrid gel into a mechanically malleable, viscoelastic matter.